Regrowth of bacterial pathogen indicators after advanced electro-osmotic dewatering of biosolids. (1st January 2014) - Navab-Daneshmand, Tala; ,; Biyela, Precious; Frigon, Dominic
Applying an electrical field for 10 min to mechanically dewatered biosolids increased dryness to 35 to 45% and reduced Escherichia coli levels to/close to detection limits. Possible reasons for the regrowth of bacterial pathogens impacted by electro-osmotic dewatering are biosolids dryness, low pH and the generation of bacterial oxidants on the anode due to high temperatures. Testing for this with aerobic and anaerobic incubations resulted in more than four logs of E. coli regrowth in 2011, when biosolids harboured higher initial counts; whereas regrowth was not observed in 2012, when biosolids had lower E. coli counts. In 2011 experiments, however, addition of a nitrate salt prior to anaerobic incubations reduced regrowth by 1.4 logs. This indicates that other NO3 − -respiring organisms could be competing with E. coli and diverting electrons away from the E. coli population. These results suggest that electro-osmotic dewatering and nitrate can play a role in controlling E. coli regrowth.